Leptin’s crucial modulatory role in regulating body mass homeostasis of high-fat-fed striped field mice (Apodemus agrarius) - Ren, Yue; Guo, Guangtong; Hou, Yu; Chen, Kuiyou; Pu, Xinsheng; Tao, Mengfan; Ren, Yunlong; Yang, Xin’gen (Frontiers in Physiology, 2025)
To investigate into the role of leptin in body mass in high-fat-fed animals. Male striped field mice (Apodemus agrarius) fed high-fat diets were given leptin (0.5 μg/g.d) via intraperitoneal injection for 28 days. Their body mass, digestive metrics, and physiological parameters of food consumption and energy metabolism were compared to those of the control and high-fat food groups. Firstly, the high-fat diet did not cause weight gain in Apodemus agrarius, and the animals on the diet ate less and had higher apparent digestibility. Furthermore, exogenous leptin injection in A. agrarius reduced food intake, increased fecal content, and reduced apparent digestibility. Additionally, exogenous leptin injection inhibited the activity of the AMPK in the hypothalamus, increased the activity of malonyl CoA, inhibited the expression of orexigenic neuropeptide mRNA, promoted the expression of anorexigenic neuropeptide mRNA, and thus reduced food intake and body mass. Finally, exogenous leptin injection increased uncoupling protein 1 content, T45′-deiodinase II activity, and cytochrome C oxidase activity in brown adipose tissue, increased serum triiodothyronine, and increased animal energy consumption. In conclusion, our data indicate that leptin affects body mass in animals on a high-fat diet in two ways: by inhibiting food intake and increasing energy expenditure.